A STUDY ON CORPUS-BASED EFL VOCABULARY TEACHING - Lu Hongyan (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
This paper introduces the development of corpus linguistics and its advantages in EFL(English as Foreigner Language) vocabulary teaching from three aspects: theapplication of corpus into the vocabulary teaching can greatly improve the efficiencyfor vocabulary teaching by providing the word frequency. And by co-presenting theactual cases of different usages and contexts of the word, the corpus can help to avoidthe negative language transfer and thus enhance the learners’ comprehension andacquisition of the vocabulary.